A catalyst for the hydrogenation of carbon dioxide to higher hydrocarbons and its preparation method
The FeCoCuAl-BTA catalyst was prepared by precipitation method, and the directional change of the catalyst surface was solved through BTA, which solved the problems of the CO2 conversion rate and high carbon hydrocarbon selectivity and yield of the existing CO2 hydrogenation catalyst, and achieved efficient CO2 conversion and high carbon hydrocarbon selectivity of the catalyst.
Patent Information
- Application Number
- CN202411992156.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing CO2 hydrogenation catalysts have poor performance in CO2 conversion and high carbon hydrocarbon selectivity and yield, and have low catalytic activity.
The FeCoCuAl-BTA catalyst was prepared by precipitation method, and the catalyst surface was changed in a directional manner through BTA to increase the pore size and dispersion of active components, thereby improving the CO2 conversion rate of the catalyst and the selectivity and yield of high carbon hydrocarbons.
The selectivity and CO2 conversion of catalysts to high carbon hydrocarbons are significantly improved, and the problems of low CO2 conversion and low carbon hydrocarbon selection and yield in the prior art are solved, and the large specific surface area and good mesoporous structure are provided.
Smart Images

Figure CN119771413A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts for resource utilization of carbon dioxide, and in particular relates to a catalyst for hydrogenating carbon dioxide to produce higher carbon hydrocarbons and a preparation method thereof. Background Art
[0002] The large-scale emission of greenhouse gases (GHG) has led to a continuous rise in the global average temperature. Among them, the most important and most emitted greenhouse gas is CO2, which accounts for more than 70% of emissions. In 2022, global carbon dioxide emissions from energy combustion and industrial processes increased by 0.9%, or 321 million tons, to a historical high of 3.68 billion tons. As the concentration of CO2 in the atmosphere gradually increases, various natural disasters and extreme climate events are becoming more and more frequent, so multiple approaches need to be taken to reduce CO2 emissions. The chemical utilization of CO2 is currently a research hotspot in the field of CO2 emission reduction. The chemical utilization of CO2 refers to the conversion of CO2 as a raw material into various valuable chemicals and fuels, which can not only achieve carbon emission reduction, but also alleviate the energy crisis to a certain extent. At present, CO2 hydrogenation technology is used to convert CO2 into high-carbon hydrocarbons (C 5+ ) has attracted widespread attention from researchers, and its key technology lies in the research and development of catalysts.
[0003] Most of the existing CO2 hydrogenation catalysts are Fe / Co monometallic or bimetallic catalysts. CO2 is mostly converted into low-carbon hydrocarbons (C2~C4) by Fischer-Tropsch synthesis (FTS). Due to the low catalytic activity of this type of catalyst, the CO2 conversion rate is not high and the yield of high-carbon hydrocarbons is extremely low. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing a catalyst for producing high-carbon hydrocarbons by hydrogenating carbon dioxide in view of the deficiencies of the above-mentioned prior art. The method adopts a precipitation method to prepare a FeCoCuAl-BTA catalyst, and by using BTA to change the directionality of the catalyst surface, pores with larger pore sizes are obtained, and the dispersion of active components is increased, thereby improving the selectivity of the catalyst for high-carbon hydrocarbons and the CO2 conversion rate and yield of the catalyst, solving the problems of low CO2 conversion rate, low selectivity and yield of high-carbon hydrocarbons, and low catalytic activity in the prior art.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a catalyst for hydrogenating carbon dioxide to produce higher carbon hydrocarbons, characterized in that the method uses Fe(NO3)3·9H2O, Co(NO3)3·9H2O, Cu(NO3)3·3H2O and Al(NO3)3·6H2O as raw materials to prepare a mixed solution of metal ions, which reacts with a precipitant and then is allowed to stand, filtered, washed, dried, crushed, impregnated, air-dried and calcined to obtain a FeCoCuAl-BTA catalyst.
[0006] The above-mentioned method for preparing a catalyst for hydrogenating carbon dioxide to produce higher carbon hydrocarbons is characterized in that the components of the FeCoCuAl-BTA catalyst include Fe3O4, CoFe2O4, CuO and Al2O3.
[0007] The above-mentioned method for preparing a catalyst for hydrogenating carbon dioxide to produce higher carbon hydrocarbons is characterized in that the method comprises the following steps:
[0008] Step 1, preparing a metal ion mixed solution using Fe(NO3)3·9H2O, Co(NO3)3·9H2O, Cu(NO3)3·3H2O and Al(NO3)3·6H2O as raw materials;
[0009] Step 2: Add BTA to the mixed alkali solution of NaOH-Na2CO3 to prepare a precipitant;
[0010] Step 3: under stirring conditions, dropwise add the precipitant prepared in step 2 to the metal ion mixed solution prepared in step 1 to perform a precipitation reaction to obtain a slurry, and then use a mixed alkali solution of NaOH-Na2CO3 to adjust the pH of the slurry to a weak alkaline state;
[0011] Step 4: continuously stirring the slurry adjusted in step 3, and then standing for aging, filtering, washing the filter cake with distilled water until it is neutral, and then drying, crushing, and sieving in sequence to obtain particles;
[0012] Step 5: Introduce potassium and sodium ions as auxiliary agents into the particles obtained in step 4 by an equal volume impregnation method, air-dry, and then calcine in air to obtain a FeCoCuAl-BTA catalyst.
[0013] The preparation process of the present invention adopts a mixed alkali solution system of NaOH-Na2CO3, and a double precipitate is formed after a precipitation reaction, and water and CO2 acidic gas are formed in the subsequent drying and roasting process, thereby further modifying the catalyst surface. At the same time, the present invention adopts a composite auxiliary agent K / Na to exert a synergistic effect, so as to improve the degree of reduction of metal ions, generate more active components, and improve the pore size and increase the specific surface area of the catalyst.
[0014] The above-mentioned method for preparing a catalyst for hydrogenating carbon dioxide to produce higher carbon hydrocarbons is characterized in that the metal ion concentration in the metal ion mixed solution in step 1 is 0.5 mol / L, and the molar ratio of Fe:Co:Cu:Al is 18:6:1:6. The present invention controls the molar ratio of each metal ion to ensure the formation of active components of a specified crystal form, so that the lattice defect sites generated by it promote the occurrence of redox reactions on the catalyst surface.
[0015] The above-mentioned method for preparing a catalyst for hydrogenating carbon dioxide to produce higher carbon hydrocarbons is characterized in that the concentration of NaOH in the mixed alkali solution of NaOH-Na2CO3 in step 2 and step 3 is 0.4 mol / L, and the concentration of Na2CO3 is 0.4 mol / L.
[0016] The above-mentioned method for preparing a catalyst for hydrogenating carbon dioxide to produce high carbon hydrocarbons is characterized in that the molar ratio of BTA added in step 2 to Fe in the metal ion mixed solution in step 1 is BTA:Fe=7.7-20.0:1. Preferably, it is 7.7:1, 9.1:1, 11.1:1, 14.3:1 or 20.0:1, and the optimal value is 20.0:1. The present invention proportions the amount of BTA according to the amount of active components, which is beneficial to increase the dispersion amount of active components while modifying the carrier.
[0017] The above-mentioned method for preparing a catalyst for hydrogenating carbon dioxide to produce higher carbon hydrocarbons is characterized in that the dripping time in step 3 is 1.5h to 2.5h, preferably 2.2h.
[0018] The above-mentioned method for preparing a catalyst for hydrogenating carbon dioxide to produce higher carbon hydrocarbons is characterized in that in step 3, the pH of the slurry is adjusted to 8 to 9, preferably 8.5.
[0019] The above-mentioned method for preparing a catalyst for hydrogenating carbon dioxide to produce higher carbon hydrocarbons is characterized in that the continuous stirring time in step 4 is 1 hour, the static aging time is 30 hours, the drying temperature is 100°C, the time is 24 hours, and the sieve used for screening is 20-40 mesh; the calcination temperature in step 5 is 500°C, and the time is 5 hours.
[0020] In addition, the present invention also discloses a catalyst for preparing higher carbon hydrocarbons by hydrogenating carbon dioxide, which is characterized in that it is prepared by the above method.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] 1. The present invention uses hydrated nitrates of Fe, Co, Cu and Al as raw materials, prepares FeCoCuAl-BTA catalyst by precipitation method, and uses BTA with suitable acidity, namely 1,3,5-benzenetricarboxylic acid, to achieve directional change on the catalyst surface. On the one hand, large-diameter pores are created on the catalyst surface with aluminum oxide as carrier, so that it is easier to synthesize high-carbon hydrocarbons (C 5+ ), thus having better selectivity for high-carbon hydrocarbons, and on the other hand increasing the dispersion of the active components, so that the active components can be better dispersed on the surface of the catalyst, thereby improving the CO2 conversion rate and yield of the catalyst, which is conducive to solving the problem of greenhouse gas control and reducing dependence on traditional fossil fuels.
[0023] 2. The catalyst for preparing high carbon hydrocarbons by hydrogenation of carbon dioxide prepared by the present invention, namely the FeCoCuAl-BTA catalyst, has a large specific surface area, which is distributed in the range of 109m 2 ·g -1 ~123m 2 ·g -1 , which is beneficial to the adsorption of CO2 and improves the CO2 conversion rate and yield of the catalyst.
[0024] 3. The catalyst for producing high carbon hydrocarbons by hydrogenation of carbon dioxide prepared by the present invention, namely the FeCoCuAl-BTA catalyst, has a good mesoporous structure with a pore size distribution of 2nm to 10nm, which is beneficial to the mass transfer of CO2 hydrogenation intermediates and improves the CO2 conversion rate of the catalyst.
[0025] 4. The catalyst for hydrogenating carbon dioxide to produce higher carbon hydrocarbons prepared by the present invention, namely the FeCoCuAl-BTA catalyst, generates metallic Fe and Fe-Co alloy after being applied to the hydrogenation reduction of carbon dioxide. Co as a structural additive can promote the formation of Fe lattice defect sites, thereby promoting the oxidation-reduction reaction on the catalyst surface, so that the catalyst exhibits better catalytic activity.
[0026] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the XRD pattern of the FeCoCuAl-BTA catalyst prepared in Examples 1 to 5 of the present invention.
[0028] Figure 2 This is the H2-TPR spectrum of the FeCoCuAl-BTA catalyst prepared in Examples 1 to 5 of the present invention.
[0029] Figure 3 This is the CO2-TPD spectrum of the FeCoCuAl-BTA catalyst prepared in Examples 1 to 5 of the present invention. DETAILED DESCRIPTION
[0030] The process of the FeCoCuAl-BTA catalyst prepared in Examples 1 to 5 of the present invention for the hydrogenation of CO2 to produce higher carbon hydrocarbons is as follows: 5 g of FeCoCuAl-BTA catalyst is loaded into a stainless steel reaction tube, and hydrogen is introduced at a flow rate of 50 mL / min for hydrogen reduction for 2 h under normal pressure and 400 ° C; the catalyst bed temperature is adjusted to 300 ° C, and the raw gas is introduced into the reaction tube at a molar ratio of H2:CO2=3:1, and the pressure is increased to 2.0 MPa, and the gas hourly space velocity is maintained at 3600 h -1 After 6 hours of continuous catalytic hydrogenation of CO2, the gas components were analyzed by gas chromatography every 30 minutes to obtain the CO2 conversion rate and high carbon hydrocarbons (C 5+ )Optional data.
[0031] Example 1
[0032] This embodiment includes the following steps:
[0033] Step 1: Using Fe(NO3)3·9H2O, Co(NO3)3·9H2O, Cu(NO3)3·3H2O and Al(NO3)3·6H2O as raw materials, a metal ion mixed solution with a metal ion concentration of 0.5 mol / L was prepared in a molar ratio of Fe:Co:Cu:Al=18:6:1:6;
[0034] Step 2, adding BTA to a mixed alkali solution of NaOH-Na2CO3 to prepare a precipitant; the concentration of NaOH in the mixed alkali solution of NaOH-Na2CO3 is 0.4 mol / L, the concentration of Na2CO3 is 0.4 mol / L, and the molar ratio of the added BTA to the Fe in the metal ion mixed solution in step 1 is BTA:Fe=7.7:1;
[0035] Step 3: under vigorous stirring conditions, the precipitant prepared in step 2 is added dropwise to the metal ion mixed solution prepared in step 1 for 2.2 hours to perform a precipitation reaction to obtain a slurry, and then a mixed alkali solution of NaOH-Na2CO3 is used to adjust the pH of the slurry to 8.5; the concentration of NaOH in the mixed alkali solution of NaOH-Na2CO3 is 0.4 mol / L, and the concentration of Na2CO3 is 0.4 mol / L;
[0036] Step 4: Stir the slurry adjusted in step 3 for 1 hour, then stand and age for 30 hours, filter and wash the filter cake with distilled water until it is neutral, then dry at 100° C. for 24 hours, crush, and pass through a 20-40 mesh sieve to obtain particles;
[0037] Step 5: Use the equal volume impregnation method and introduce auxiliary potassium and sodium ions into the particles obtained in step 4 at a molar ratio of Fe:K:Na=18.00:1.67:0.61. After air-drying, place them in a muffle furnace and calcine them at 500°C in air for 5 hours to obtain a FeCoCuAl-BTA catalyst, recorded as FeCoCuAl-7.7BTA.
[0038] After testing, the CO2 conversion rate of FeCoCuAl-7.7BTA prepared in this example is 60%, and the high carbon hydrocarbon (C 5+ ) The selectivity is 26% and the yield is 15.6%.
[0039] Example 2
[0040] This embodiment includes the following steps:
[0041] Step 1: Using Fe(NO3)3·9H2O, Co(NO3)3·9H2O, Cu(NO3)3·3H2O and Al(NO3)3·6H2O as raw materials, a metal ion mixed solution with a metal ion concentration of 0.5 mol / L was prepared in a molar ratio of Fe:Co:Cu:Al=18:6:1:6;
[0042] Step 2, adding BTA to a mixed alkali solution of NaOH-Na2CO3 to prepare a precipitant; the concentration of NaOH in the mixed alkali solution of NaOH-Na2CO3 is 0.4 mol / L, the concentration of Na2CO3 is 0.4 mol / L, and the molar ratio of the added BTA to the Fe in the metal ion mixed solution in step 1 is BTA:Fe=9.1:1;
[0043] Step 3: under vigorous stirring conditions, the precipitant prepared in step 2 is added dropwise to the metal ion mixed solution prepared in step 1 for 2.2 hours to perform a precipitation reaction to obtain a slurry, and then a mixed alkali solution of NaOH-Na2CO3 is used to adjust the pH of the slurry to 8.5; the concentration of NaOH in the mixed alkali solution of NaOH-Na2CO3 is 0.4 mol / L, and the concentration of Na2CO3 is 0.4 mol / L;
[0044] Step 4: Stir the slurry adjusted in step 3 for 1 hour, then stand and age for 30 hours, filter and wash the filter cake with distilled water until it is neutral, then dry at 100° C. for 24 hours, crush, and pass through a 20-40 mesh sieve to obtain particles;
[0045] Step 5: Using an equal volume impregnation method and a molar ratio of Fe:K:Na = 18.00:1.67:0.61, the particles obtained in step 4 are introduced with auxiliary potassium and sodium ions. After air-drying, the particles are placed in a muffle furnace and calcined at 500°C in air for 5 hours to obtain a FeCoCuAl-BTA catalyst, recorded as FeCoCuAl-9.1BTA; the components of the FeCoCuAl-BTA catalyst include Fe3O4, CoFe2O4, CuO and Al2O3.
[0046] After testing, the CO2 conversion rate of FeCoCuAl-9.1BTA prepared in this example is 62%, and the high carbon hydrocarbon (C 5+ ) The selectivity is 31% and the yield is 19.22%.
[0047] Example 3
[0048] This embodiment includes the following steps:
[0049] Step 1: Using Fe(NO3)3·9H2O, Co(NO3)3·9H2O, Cu(NO3)3·3H2O and Al(NO3)3·6H2O as raw materials, a metal ion mixed solution with a metal ion concentration of 0.5 mol / L was prepared in a molar ratio of Fe:Co:Cu:Al=18:6:1:6;
[0050] Step 2, adding BTA to a mixed alkali solution of NaOH-Na2CO3 to prepare a precipitant; the concentration of NaOH in the mixed alkali solution of NaOH-Na2CO3 is 0.4 mol / L, the concentration of Na2CO3 is 0.4 mol / L, and the molar ratio of the added BTA to the Fe in the mixed metal ion solution in step 1 is BTA:Fe=11.1:1;
[0051] Step 3: under vigorous stirring conditions, the precipitant prepared in step 2 is added dropwise to the metal ion mixed solution prepared in step 1 for 2.2 hours to perform a precipitation reaction to obtain a slurry, and then a mixed alkali solution of NaOH-Na2CO3 is used to adjust the pH of the slurry to 8.5; the concentration of NaOH in the mixed alkali solution of NaOH-Na2CO3 is 0.4 mol / L, and the concentration of Na2CO3 is 0.4 mol / L;
[0052] Step 4: Stir the slurry adjusted in step 3 for 1 hour, then stand and age for 30 hours, filter and wash the filter cake with distilled water until it is neutral, then dry at 100° C. for 24 hours, crush, and pass through a 20-40 mesh sieve to obtain particles;
[0053] Step 5: Use the equal volume impregnation method and introduce auxiliary potassium and sodium ions into the particles obtained in step 4 at a molar ratio of Fe:K:Na=18.00:1.67:0.61. After air-drying, place them in a muffle furnace and calcine them at 500°C in air for 5 hours to obtain a FeCoCuAl-BTA catalyst, recorded as FeCoCuAl-11.1BTA.
[0054] After testing, the CO2 conversion rate of FeCoCuAl-11.1BTA prepared in this example is 66%, and the high carbon hydrocarbons (C 5+ ) The selectivity is 33% and the yield is 21.78%.
[0055] Example 4
[0056] This embodiment includes the following steps:
[0057] Step 1: Using Fe(NO3)3·9H2O, Co(NO3)3·9H2O, Cu(NO3)3·3H2O and Al(NO3)3·6H2O as raw materials, a metal ion mixed solution with a metal ion concentration of 0.5 mol / L was prepared in a molar ratio of Fe:Co:Cu:Al=18:6:1:6;
[0058] Step 2, adding BTA to a mixed alkali solution of NaOH-Na2CO3 to prepare a precipitant; the concentration of NaOH in the mixed alkali solution of NaOH-Na2CO3 is 0.4 mol / L, the concentration of Na2CO3 is 0.4 mol / L, and the molar ratio of the added BTA to the Fe in the metal ion mixed solution in step 1 is BTA:Fe=14.3:1;
[0059] Step 3: under vigorous stirring conditions, the precipitant prepared in step 2 is added dropwise to the metal ion mixed solution prepared in step 1 for 2.2 hours to perform a precipitation reaction to obtain a slurry, and then a mixed alkali solution of NaOH-Na2CO3 is used to adjust the pH of the slurry to 8.5; the concentration of NaOH in the mixed alkali solution of NaOH-Na2CO3 is 0.4 mol / L, and the concentration of Na2CO3 is 0.4 mol / L;
[0060] Step 4: Stir the slurry adjusted in step 3 for 1 hour, then stand and age for 30 hours, filter and wash the filter cake with distilled water until it is neutral, then dry at 100° C. for 24 hours, crush, and pass through a 20-40 mesh sieve to obtain particles;
[0061] Step 5: Use the equal volume impregnation method and introduce auxiliary potassium and sodium ions into the particles obtained in step 4 at a molar ratio of Fe:K:Na=18.00:1.67:0.61. After air-drying, place them in a muffle furnace and calcine them at 500°C in air for 5 hours to obtain a FeCoCuAl-BTA catalyst, recorded as FeCoCuAl-14.3BTA.
[0062] After testing, the CO2 conversion rate of FeCoCuAl-14.3BTA prepared in this example is 68%, and the high carbon hydrocarbon (C 5+ ) The selectivity is 34% and the yield is 23.12%.
[0063] Example 5
[0064] This embodiment includes the following steps:
[0065] Step 1: Using Fe(NO3)3·9H2O, Co(NO3)3·9H2O, Cu(NO3)3·3H2O and Al(NO3)3·6H2O as raw materials, a metal ion mixed solution with a metal ion concentration of 0.5 mol / L was prepared in a molar ratio of Fe:Co:Cu:Al=18:6:1:6;
[0066] Step 2, adding BTA to a mixed alkaline solution of NaOH-Na2CO3 to prepare a precipitant; the concentration of NaOH in the mixed alkaline solution of NaOH-Na2CO3 is 0.4 mol / L, the concentration of Na2CO3 is 0.4 mol / L, and the molar ratio of the added BTA to the Fe in the metal ion mixed solution in step 1 is BTA:Fe=20.0:1;
[0067] Step 3: under vigorous stirring conditions, the precipitant prepared in step 2 is added dropwise to the metal ion mixed solution prepared in step 1 for 2.2 hours to perform a precipitation reaction to obtain a slurry, and then a mixed alkali solution of NaOH-Na2CO3 is used to adjust the pH of the slurry to 8.5; the concentration of NaOH in the mixed alkali solution of NaOH-Na2CO3 is 0.4 mol / L, and the concentration of Na2CO3 is 0.4 mol / L;
[0068] Step 4: Stir the slurry adjusted in step 3 for 1 hour, then stand and age for 30 hours, filter and wash the filter cake with distilled water until it is neutral, then dry at 100° C. for 24 hours, crush, and pass through a 20-40 mesh sieve to obtain particles;
[0069] Step 5: Use the equal volume impregnation method and introduce auxiliary potassium and sodium ions into the particles obtained in step 4 at a molar ratio of Fe:K:Na=18.00:1.67:0.61. After air-drying, place them in a muffle furnace and calcine them at 500°C in air for 5 hours to obtain a FeCoCuAl-BTA catalyst, recorded as FeCoCuAl-20.0BTA.
[0070] After testing, the CO2 conversion rate of FeCoCuAl-20.0BTA prepared in this example is 70%, and the high carbon hydrocarbon (C 5+ ) The selectivity was 42% and the yield was 29.4%.
[0071] Figure 1 The XRD patterns of the FeCoCuAl-BTA catalysts prepared in Examples 1 to 5 of the present invention are as follows: Figure 1 It can be seen that characteristic diffraction peaks can be observed at 2θ=30.3°, 35.8°, 57.6°, and 63.1° in each FeCoCuAl-BTA catalyst, which are attributed to Fe3O4 (standard card PDF No: 65-3107) or CoFe2O4 (standard card PDF No: 2-1045), and with the increase of BTA content, these characteristic diffraction peak signals gradually weaken; the diffraction peaks at 2θ=44.7° and 64.7° correspond to elemental Fe (standard card PDF No: 1-12 62), and the diffraction peak signal gradually increased. When B / Fe=20.0%, i.e., Example 5, the diffraction peak signal was the strongest. This indicates that after the introduction of BTA into the catalyst, the crystallinity of Fe3O4 / CoFe2O4 in the catalyst was reduced, so that more active metals had the opportunity to be reduced, and the degree of reduction was further deepened. Metallic Fe is the main active substance in the catalytic hydrogenation reaction. It can react with CO bonds to generate iron carbide substances such as Fe5C2, thereby promoting the production of hydrocarbon substances and providing a basis for the further conversion of low-carbon hydrocarbons to high-carbon hydrocarbons.
[0072] Figure 2 The H2-TPR spectrum of the FeCoCuAl-BTA catalyst prepared in Examples 1 to 5 of the present invention, from Figure 2 It can be seen that the reduction peaks of each catalyst appear around 353°C. Figure 1 It can be inferred that this is related to Fe 3+ →Fe 0 At the same time, with the increase of BTA content, the reduction peak of the catalyst moves from 363 °C to 310 °C, indicating that the reduction temperature of the catalyst decreases, indicating that the increase of BTA content will weaken the interaction between the components in the catalyst, making the catalyst easier to be reduced, which is consistent with the XRD spectrum of the BTA-doped FeCoCuAl catalyst after reduction. Figure 1The results are consistent.
[0073] Figure 3 The CO2-TPD spectra of the FeCoCuAl-BTA catalysts prepared in Examples 1 to 5 of the present invention are shown in FIG. Figure 3 It can be seen that each catalyst has three main CO2 desorption peaks, which are around 69°C, 166°C and 607.8°C respectively. The CO2 desorption peak at low temperature corresponds to the physical adsorption desorption peak, and the CO2 desorption peak at medium and high temperature corresponds to the medium-intensity chemical adsorption desorption peak. With the increase of BTA content, the desorption peak area also increases, indicating that the introduction of BTA in the catalyst can improve the adsorption capacity of the catalyst for CO2. This is because with the increase of organic BTA content, the number of micropores on the catalyst surface increases, which increases the adsorption amount of CO2 and promotes the formation of Fe-C bonds, thereby improving the reaction activity of the catalyst. At the same time, the Fe element generated by the catalyst reduction provides electrons to CO2, and the activated and stable CO2 molecules promote the RWGS reaction.
[0074] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a catalyst for hydrogenating carbon dioxide to produce higher carbon hydrocarbons, characterized in that: The method uses Fe(NO3)3·9H2O, Co(NO3)3·9H2O, Cu(NO3)3·3H2O and Al(NO3)3·6H2O as raw materials to prepare a metal ion mixed solution, which reacts with a precipitant, and then is allowed to stand, filtered, washed, dried, crushed, impregnated, air-dried and calcined to obtain a FeCoCuAl-BTA catalyst.
2. The method for preparing a catalyst for hydrogenating carbon dioxide to produce higher carbon hydrocarbons according to claim 1, characterized in that: The components of the FeCoCuAl-BTA catalyst include Fe3O4, CoFe2O4, CuO and Al2O3.
3. The method for preparing a catalyst for hydrogenating carbon dioxide to produce higher carbon hydrocarbons according to claim 1, characterized in that: The method comprises the following steps: Step 1, preparing a metal ion mixed solution using Fe(NO3)3·9H2O, Co(NO3)3·9H2O, Cu(NO3)3·3H2O and Al(NO3)3·6H2O as raw materials; Step 2: Add BTA to the mixed alkali solution of NaOH-Na2CO3 to prepare a precipitant; Step 3: under stirring conditions, dropwise add the precipitant prepared in step 2 to the metal ion mixed solution prepared in step 1 to perform a precipitation reaction to obtain a slurry, and then use a mixed alkali solution of NaOH-Na2CO3 to adjust the pH of the slurry to a weak alkaline state; Step 4: continuously stirring the slurry adjusted in step 3, and then standing for aging, filtering, washing the filter cake with distilled water until it is neutral, and then drying, crushing, and sieving in sequence to obtain particles; Step 5: Introduce potassium and sodium ions as auxiliary agents into the particles obtained in step 4 by an equal volume impregnation method, air-dry, and then calcine in air to obtain a FeCoCuAl-BTA catalyst.
4. The method for preparing a catalyst for hydrogenating carbon dioxide to produce higher carbon hydrocarbons according to claim 3, characterized in that: The metal ion concentration in the metal ion mixed solution in step 1 is 0.5 mol / L, and the molar ratio of Fe:Co:Cu:Al is 18:6:1:
6.
5. The method for preparing a catalyst for hydrogenating carbon dioxide to produce higher carbon hydrocarbons according to claim 3, characterized in that: In step 2 and step 3, the concentration of NaOH in the mixed alkaline solution of NaOH-Na2CO3 is 0.4 mol / L, and the concentration of Na2CO3 is 0.4 mol / L.
6. The method for preparing a catalyst for hydrogenating carbon dioxide to produce higher carbon hydrocarbons according to claim 3, characterized in that: The molar ratio of BTA added in step 2 to Fe in the metal ion mixed solution in step 1 is BTA:Fe=7.7-20.0:
1.
7. The method for preparing a catalyst for hydrogenating carbon dioxide to produce higher carbon hydrocarbons according to claim 3, characterized in that: The dropping time in step 3 is 1.5h to 2.5h.
8. The method for preparing a catalyst for hydrogenating carbon dioxide to produce higher carbon hydrocarbons according to claim 3, characterized in that: In step 3, the pH of the slurry is adjusted to 8-9.
9. The method for preparing a catalyst for hydrogenating carbon dioxide to produce higher carbon hydrocarbons according to claim 3, characterized in that: The continuous stirring time in step 4 is 1 hour, the static aging time is 30 hours, the drying temperature is 100° C., the time is 24 hours, and the sieve used for screening is 20-40 mesh; the roasting temperature in step 5 is 500° C., and the time is 5 hours.
10. A catalyst for hydrogenating carbon dioxide to produce higher carbon hydrocarbons, characterized in that: The method is prepared by any one of claims 1 to 9.